Valoración de sulfuros y fosfatos presentes en agua de pozos de la Parroquia El Cambio, cantón Machala. - Macao Solorzano, Ángeles E (2010)
This investigation was realized on well point waters from El Cambio neighborhood, Machala city, El Oro province to analyze concentration values of hydrogen sulfide and phosphates and to compare with optimal norms and establish chemical contamination grade from the place.